A new five-wavelength photometer operated in Tromsø (69.6°N, 19.2°E) - Nozawa, Satonori; Kawabata, Tetsuya; Hosokawa, Keisuke; Ogawa, Yasunobu; Tsuda, Takuo; Mizuno, Akira; Fujii, Ryoichi; Hall, Chris (Earth, Planets and Space, 2018)
Source at https://doi.org/10.1186/s40623-018-0962-x. © The Author(s) 2018 A new fve-wavelength photometer was developed and installed at the EISCAT Tromsø site (69.6°N, 19.2°E) in January 2017. The photometer consists of two units: an optical unit and a control unit together with a PC. The photometer is capable of simultaneously observing auroral emissions with fve wavelengths. A uniqueness of the present system is its capability of precise pointing, which enables pointing the photometer at the feld-aligned position using a star image obtained with a coaxial digital camera. Another uniqueness of the system is its capability of taking data at a sampling rate of 400 Hz. Some preliminary results including correlations between 427.8 nm and 557.7 nm, 630 nm, 777.4 nm, and 844.6 nm are presented. These comparisons are not signifcant unless all of the fve wavelength emissions emanated from exactly the same volume (i.e., magnetic zenith) in the ionosphere, which the present system has.